2002
DOI: 10.1021/om010530j
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Polymerization Behavior of Tris(pyrazolyl)borate Titanium(IV) Complexes

Abstract: A set of Tp′TiCl 3 and Tp′TiCl 2 (OR) complexes containing tris(pyrazolyl)borate ligands with diverse steric properties has been evaluated for ethylene polymerization under MAO activation conditions (Tp′ ) HB(3-mesitylpyrazolyl) 2 (5-mesitylpyrazolyl) -(Tp Ms* ), HB(3mesitylpyrazolyl) 3 -(Tp Ms ), HB(3,5-Me 2 -pyrazolyl) 3 -(Τp * ), HB(pyrazolyl) 3 -(Tp), BuB(pyrazolyl) 3 -( Bu Tp)). The activity of Tp′TiX 3 /MAO varies in the order Tp Ms* TiCl 3 (10c) >

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 124 publications
(82 citation statements)
references
References 66 publications
7
72
2
1
Order By: Relevance
“…On the basis of the powder X-ray diffraction (XRD) analysis, it was observed that the basal spacing of the predried C30B changes from 1.85 nm (2θ = 4.8) to 2.18 nm (2θ = 4.0) indicating that the intercalation of the titanium catalyst into the clay gallery took place (Figure 1). In this case, the increased spacing from predried C30B to 1/C30B is consistent with the 34 The ethylene polymerization behavior of 1/C30B has been evaluated using methylaluminoxane (MAO) as cocatalyst. Representative results are given in Table 1.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…On the basis of the powder X-ray diffraction (XRD) analysis, it was observed that the basal spacing of the predried C30B changes from 1.85 nm (2θ = 4.8) to 2.18 nm (2θ = 4.0) indicating that the intercalation of the titanium catalyst into the clay gallery took place (Figure 1). In this case, the increased spacing from predried C30B to 1/C30B is consistent with the 34 The ethylene polymerization behavior of 1/C30B has been evaluated using methylaluminoxane (MAO) as cocatalyst. Representative results are given in Table 1.…”
Section: Resultssupporting
confidence: 76%
“…34 Thus, the predried C30B reacted with toluene solution of Tp Ms* TiCl 3 (1) for 24 h to generate the intercalated titanium catalyst 1/C30B (Scheme 1). The resulting metal content on the clay determined by ICP-OES was 20 µmol Ti g -1 of clay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethylene polymerization behavior using catalysts 3, 4 and 5 were studied under different reaction times (Table 1, entries 20-34) and temperatures (entries [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. The highest activity of catalyst 5 was obtained at 10 °C (31200 Kg PE mol cat -1 h -1 ).…”
Section: Effects Of Polymerization Conditionsmentioning
confidence: 99%
“…In consequence, quite a few highly active catalysts based on both early and late transition metal complexes have been developed [7][8][9][10][11][12][13][14]. There are, however, only a few examples of titanium complexes displaying high ethylene polymerization activities [15][16][17][18][19], though titanium metal is the major player in highly active heterogeneous Ziegler-Natta catalysts. Accordingly, further researches have been conducted on titanium catalysts with the intention of developing the highly active titanium catalysts and applying them to the polymerization of ethylene.…”
Section: Introductionmentioning
confidence: 99%